Chloride ion penetration behaviour in concrete containing an expansive additive and a calcium-aluminate-based additive - Shinya Ito; Takeshi Iyoda (Acta Polytechnica CTU Proceedings, 2022)
The effect of the material characteristics on the infiltration behaviour of chloride ions in concrete containing a combination of an expansive additive and a calcium-aluminate-based additive has been investigated. The same level of salt resistance as that of blast furnace slug cement was exhibited even for a small addition amount. In addition, the permeation behaviour of chloride ions was largely influenced by the immobilisation capacity and pore network. When these changes were dominant, the results suggested that the characteristics based on the Fick diffusion equations may not necessarily reproduce the actual permeation behaviour of chloride ions.